2004
DOI: 10.1017/s135561770410413x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and nonemotional facial expressions in people with Parkinson's disease

Abstract: We investigated facial expressivity in 19 people with Parkinson's disease (PD; 14 men and 5 women) and 26 healthy controls (13 men and 13 women). Participants engaged in experimental situations that were designed to evoke emotional facial expressions, including watching video clips and holding conversations, and were asked to pose emotions and imitate nonemotional facial movements. Expressivity was measured with subjective rating scales, objective facial measurements (Facial Action Coding System), and self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 30 publications
9
69
2
Order By: Relevance
“…Voluntary orofacial movements are smaller in amplitude and slower in velocity in PD, possibly influencing the release of facial emotions [2]. Expressiveness of spontaneous facial emotions, rated by subjective rating scales or objective computerized methods, has been consistently reported to be impaired in PD [3][4][5], while expressiveness of posed facial emotions has been reported either normal [4] or impaired [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voluntary orofacial movements are smaller in amplitude and slower in velocity in PD, possibly influencing the release of facial emotions [2]. Expressiveness of spontaneous facial emotions, rated by subjective rating scales or objective computerized methods, has been consistently reported to be impaired in PD [3][4][5], while expressiveness of posed facial emotions has been reported either normal [4] or impaired [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability to express disgust correlated with the recognition of facial emotions, in the context of a preserved ability to describe and recognized their own feelings (i.e. no alexithymia).It is still unclear whether the ability to voluntarily pose facial emotion expression is impaired in PD, with a number of studies suggesting that it is spared[4] while other studies have showed that it is altered [5]…”
mentioning
confidence: 99%
“…Two studies aimed at exploring emotional facial expressivity in PD patients in tasks such as viewing emotional film excerpts, found that the patients assessed the emotional intensity of the excerpts as the same way as healthy controls in spite of reduced expressiveness, thus suggesting unaltered subjective emotional experience [22,23]. However, blunted emotional reactivity in PD has been suggested on the basis of reduced physiological arousal and/or reduced arousal ratings of aversive or highly arousing pictures as compared to healthy controls [11,12,24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the most adverse effects of living with PD is reported to be its impact on an individual's social interactions (Schrag et al, 2000;Shreurs et al, 2000). This may relate to common symptoms of Parkinson's such as masked facial expressions and speech problems, which make it harder for others to communicate and leave open the way for social misunderstanding (Lyons & Tickle-Degnen, 2003;Simons, Pasqualini, Reddy, & Wood, 2004). It could also relate to those with PD being more likely to withdraw from social contact because of embarrassment, perceived communication difficulties or other issues relating to their illness.…”
Section: Introductionmentioning
confidence: 99%